Positive effect of ethanol-induced Lactococcus lactis on alcohol metabolism in mice - Sisi Chen; Shimin Jia; Keke Suo; Qiaozhen Kang; Limin Hao; Laizheng Lu; Xin Liu; Jinyong Huang; Jike Lu (Food Science and Human Wellness)
It is well known that exposure to environmental stresses could enhance the adaptability of bacteria and up-regulate the expression of a variety of oxidative stress-related genes and antioxidant enzymes. It is unclear whether the adaptability of microorganisms formed naturally in special environments could transfer to other organisms. The study aimed to evaluate the effects of untreated and ethanol-induced Lactococcus lactis intracellular extracts (U-IE and E-IE) on alcohol metabolism in mice. The positive effects of E-IE on alcohol metabolism in mice were revealed by the enhanced latency of loss of righting reflex (LORR), the reduced duration of LORR, the decrease of blood alcohol concentration, as well as the elevation of alcohol dehydrogenase (ADH) activities in the stomach and liver tissues. Furthermore, the potential benefits of E-IE on the liver were evaluated by biochemical parameters including the activities of serum transaminase, the levels of antioxidant enzymes, and the pathological changes of liver tissue. The present work put forward a new point that appropriate ethanol stress could enhance the intracellular ADH activity of L. lactis, and its intracellular extracts could continue to enhance alcohol metabolism in mice.